Examining Student Wellness for the Development of Campus-Based Wellness Programs - Alexia F. Franzidis; Steven M. Zinder (The Ohio State University Libraries, 2019)
Background: Despite the many campus-based wellness programs and services offered through entities such as student services, many U.S. students lack the strategies, skills, or support systems to manage stress or change pre-existing behaviors, resulting in unhealthy behaviors and poor overall wellness. Since patterns developed during this time can form a solid foundation for future health behaviors, there is a need to develop and design wellness programs that stimulate positive health-behavior change. Aim: The purpose of this study was to assess student wellness of college students at a four-year public university to inform campus-based health programs, events, and services. Methods: An anonymous, single-structured survey was administered at an on-campus event (N = 225). The instrument covered six dimensions of wellness: physical wellness, social wellness, intellectual wellness, emotional wellness, spiritual wellness, and environmental wellness. Results: Significant differences for gender were found in the dimensions of social wellness, emotional wellness, and physical wellness.  Females reported higher levels of social and emotional wellness, while males reported higher levels of physical wellness. Differences in age for emotional wellness, and year of study for physical wellness were also found. Conclusions: Findings provide insight to direct interventions and programs that would enhance students' wellness knowledge and behaviors.